Pengaruh Influencer Marketing, Kualitas Produk Dan Harga Terhadap Kepuasan Konsumen Generasi Z Di Marketplace Online (Studi Kasus Pada Pengguna Tiktok Shop Di Kecamatan Singosari) - Rizka Angelia Febrianty; Muhammad Ridwan Basalamah; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to examine the simultaneous and partial effects of influencer marketing, product quality, and price on the consumer satisfaction of Generation Z on the TikTok Shop online marketplace. Utilizing a quantitative approach, a sample 95 respondents was selected through proportional sampling techniques in the Singosari District. The result indicate that, simultaneously, these three variables have a significant impact on consumer satisfaction, contributing 61.3% to the total variance. Partially, influencer marketing, product quality, and price each exert a positive and significant influence, with price being identified as the most dominant factor. Keywords: Influencer Marketing, Product Quality, Price, Consumer Satisfaction, Generation Z.